Measurement of Sub Foveal Choroidal Thickness in Patients with Hypertension - Fawad Ahmad Khan; Zulfiqar Uddin Syed; Taimoor Ashraf Khan; Usman Tariq; Muhammad Jahanzaib; Muhammad Saad Naseer (Pakistan Armed Forces Medical Journal, 2026)
Objective: To measure sub-foveal choroidal thickness variability in adolescent people with systemic arterial hypertension. Study Design: Comparative Cross Sectional study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan from May to Dec 2023. Methodology: This study recruited 15 young hypertensive subjects and 15 healthy control persons. Choroidal thickness was estimated using swept source- 3D optical coherence tomography. Choroidal thickness was only checked at the sub foveal site. Mercury sphygmomanometer was used to check systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) was calculated. Statistical analysis between the groups was only applied on left eye values. Results: A total of 30 individuals were included in the study, 15 in each group. The median systolic blood pressure of the Cases was 140.00 mmHg (148.00-137.00) while in Control Group was 127.00 mmHg (143.00-118.00). Similarly, the median diastolic blood of the Cases was 90.00 mmHg (94.00-87.00) and in Control Group was 84.00 mmHg (92.00-76.00). There was significant difference in the median Intraocular pressure of both the Study Groups [Cases: 105.00 mmHg (110.00-99.00) vs. Control: 96.00 mmHg (102.00-88.00); p=0.004]. The median Sub foveal Choroidal thickness of the Cases was 279.00 mmHg (288.00-269.00) and in Controls was 290.00 mm Hg (299.00-280.00). Conclusions: The outcomes of this research showed that subfoveal choroidal thickness reduces in people with systemic arterial hypertension. This can be due to arteriolar sclerosis and narrowing due to raised vascular pressure in the choroid.